(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2023)
The History Ministerial Task Team Report (HMTT) on the proposed compulsory school history in South Africa was made public in February 2018. Ever since, it has generated many debates and concerns among in- and pre-service history educators, History (of) Education scholars as well as the general public. Many of these concerns are premised on the fear that there is an attempt, at least by the state, through the work of the HMTT to (re)capture school history. This (re)capture, some argue, would deliver a school history that is both nationalist and patriotic in its approach, and glorifies only the African National Congress’s (ANC) role in history, much in the same way as the apartheid curriculum glorified the role of the National Party (NP), Afrikaner nationalism and white supremacy thinking. However, we are convinced that there might as well be a different reading of the HMTT and its Report; thus, a different form of (re)capture. In this paper, we will explore, theorise and reflect on the HMTT’s work and Report, as well as recent scholarly debates regarding the HMTT itself and its Report. This we do by employing the notion of (re)capture as our theoretical framework which is derived from the current ‘state capture’ discourse in South Africa. We then use this theoretical lens to review literature on the contested epistemic nature of school history, as well as to read and make sense of the HMTT and its Report. We conclude that those who argue that there are indeed attempts to (re)capture the school history for narrow nationalistic aspirations which are nativist in nature, provide us with a different reading of the HMTT and its report. We contend that the form of (re)capture advanced by the HMTT, and its Report is for a greater cause related to current calls for decolonisation and Africanisation of school history in post-apartheid South Africa — where the colonised ways of knowing and being can also take centre stage in the historical literature and where cognitive, epistemic, existential, and ontological justice is realised.